Design of a Novel Fab‐Like Antibody Fragment with Enhanced Stability and Affinity for Clinical use (Small Methods 2/2022). Issue 2 (17th February 2022) - Wang, Chunyu; Hong, Jiaxu; Yang, Zhenlin; Zhou, Xujiao; Yang, Yuhan; Kong, Yu; Chen, Binfan; Wu, Huifang; Qian, Bin‐Zhi; Dimitrov, Dimiter S.; Zhou, Xingtao; Wu, Yanling; et al.
Abstract : Front Cover In article number 2100966, Hong, Wu, Ying and coworkers provide a novel approach to antibody design in which the CH1 and CL domains of Fab were replaced by the engineered IgG1 CH3 domains. This novel Fab‐like antibody fragment, designated as FabCH3, has higher stability and antigen‐binding affinity than the parental Fab. The superior efficacy of FabCH3 over Fab has also been demonstrated in vivo.